COVID-19 impact on Surgical Training and Recovery Planning (COVID-STAR) - A cross-sectional observational study. (April 2021) - ,; Clements, Joshua Michael; Burke, Josh; Nally, Deirdre; Rabie, Mohamed; Kane, Elizabeth; Barlow, Emma; Mohamed, Walid; King, Martin; McClymont, Liusaidh; George, Manish; Tolofari, Sotonye; et al.
Abstract: Background: The COVID-19 pandemic has resulted in significant changes to healthcare systems which impact the delivery of surgical training. This study aimed to investigate the qualitative impact of COVID-19 on surgical training in the United Kingdom (UK) & Republic of Ireland (ROI) Methods: This national, collaborative, cross-sectional study involving 13 surgical trainee associations distributed a pan-surgical specialty questionnaire on the impact of COVID-19 on surgical training over 4 weeks in May 2020. Various aspects of training were assessed. Results: 810 completed responses were analysed (males = 401, females = 390) from all deaneries and training grades. The perceived negative overall impact of the pandemic on surgical training experience was significant. (Weighted average = 8.66). 41% of respondents (n = 301) were redeployed with 74% redeployed for >4 weeks. Complete loss of training was reported in elective operating (69.5%), outpatient activity (67.3%) and endoscopy (69.5%). A reduction of >50% was reported in emergency operating (48%) and completion of work-based assessments (WBAs) (46%). 3.3% (n = 17) of respondents reported plans to leave medicine altogether. Cancellations in study leave and regional teaching programmes without rescheduling were reported in 72% and 60% of the cohort respectively. Elective operative exposure and WBAs completion were the primary reported factors affecting potential trainee progression. Only 9% of trainees reported that they would definitely meet all required competencies. Conclusion: COVID-19 has had a negative impact on surgical training across all grades and specialties, with implications for trainee progression, recruitment and retention of the surgical workforce. Further investigation of the long-term impact at a national level is required. Highlights: The COVID-STAR study has demonstrated an overall negative immediate impact on surgical training. Redeployment to non-surgical environments was prevalent with limited educational value. The COVID-19 pandemic has changed the delivery of surgical services. Virtual education and learning modalities are being used with increasing frequency. COVID-19 has negative implications for recruitment and retention of the surgical workforce.